Vegetative traits can predict flowering quality in Phalaenopsis orchids despite large genotypic variation in response to light and temperature. - Evelien van Tongerlo (Public Library of Science (PLoS), 2021)
Phalaenopsis is an economically important horticultural ornamental, but its growth is slow and costly. The vegetative cultivation phase is long and required to ensure sufficient plant size. This is needed to develop high quality flowering plants. We studied the effects of temperature (27 or 31 °C) and light intensity (60 or 140 μmol m-2 s-1) on plant growth and development during the vegetative cultivation phase in two experiments, with respectively 19 and 14 genotypes. Furthermore, the after-effects of treatments applied during vegetative growth on flowering traits were determined. Increasing light intensity in the vegetative phase accelerated both vegetative plant growth and development. Increasing temperature accelerated vegetative leaf appearance rate, but strongly reduced plant and root biomass accumulation when temperatures were too high. Flowering was greatly affected by treatments applied during vegetative growth, and increased light and temperature increased number of flower spikes, and number of flowers and buds. Genotypic variation was large in Phalaenopsis, especially in traits related to flowering, thus care is needed when generalising results based on a limited number of cultivars. Plant biomass and number of leaves during vegetative growth were positively correlated with flowering quality. These traits can be used as an early predictor for flowering capacity and quality of the final product. Additionally, this knowledge can be used to improve selection of new cultivars.